Barbed-wire imperialism : Britain's empire of camps, 1876-1903 - Forth, Aidan (Oakland, California : University of California Press, 2017)
"Some of the world's first refugee camps and concentration camps appeared in the British Empire in the late 19th century. Famine camps detained emaciated refugees and billeted relief applicants on public works projects; plague camps segregated populations suspected of harboring disease and accommodated those evacuated from unsanitary locales; concentration camps during the Anglo-Boer War, meanwhile, adapted a technology of colonial welfare in the context of war. Wartime camps in South Africa were simultaneously instruments of military violence and humanitarian care. While providing food and shelter to destitute refugees and disciplining and reforming a population cast as uncivilized and unhygienic, British officials in South Africa applied a developing set of imperial attitudes and approaches that also governed the development of plague and famine camps in India. More than the outcomes of military counterinsurgency, Boer War camps were registers of cultural discourses about civilization, class, gender, racial purity and sanitary pollution. Although British spokesmen regarded camps as hygienic enclaves, epidemic diseases decimated inmate populations creating a damaging political scandal. In order to curb mortality and introduce order, the British government mobilized a wide variety of disciplinary and sanitary lessons assembled at Indian plague and famine camps and at other kindred institutions like metropolitan workhouses. Authorities imported officials from India with experience managing plague and famine camps to systematize and rationalize South Africa's wartime concentration camps. Ultimately, improvements to inmates' health and well-being served to legitimize camps as technologies of liberal empire and biopolitical security"--Provided by publisher.
Introduction : Britain's empire of camps -- Concentrating the "dangerous classes" : the cultural and material foundations of British camps -- "Barbed wire deterrents" : detention and relief at Indian famine campus, 1876-1901 -- "A source of horror and dread" : plague camps in Indian and South Africa, 1896-1901 -- Concentrated humanity : the management and anatomy of colonial campus, c. 1900 -- Camps in a time of war : civilian concentration in southern Africa, 1900-1901 -- "Only matched in times of famine and plague" : life and death in the concentration camps -- "A system steadily perfected" : camp reform and the "new geniuses from India", 1901-1903 -- Epilogue : Camps go global : lessons, legacies, and forgotten solidarities.
Keywords: Concentration camps -- Africa -- 19th century; South African War, 1899-1902 -- Concentration camps; Concentration camps -- India -- 19th century; Great Britain -- Colonies -- Africa -- 19th century; Great Britain -- Colonies -- India -- 19th century